Measuring Psychological Change and Predicting Recidivism Following the Swedish One-to-One Program - Berman, Anne H.; Gajecki, Mikael; Morien, Per; Priestley, Philip (Frontiers in Psychiatry, 2019)
The One-to-One program aims to reduce criminal recidivism among prisoners shortly awaiting release, and among probationers. Of 1484 program participants in Sweden, 776 contained adequate data for analysis. Pre- and post-program scores were available for the Alternative Thinking Test, Levenson’s Locus of Control Scale, Skill Survey, Citizen Scale and Problem Checklist, all areas addressed in the program. This study examined predictive properties of test scores and background characteristics regarding recidivism, as well as differences between sub-groups. All post-tests indicated pro-social changes. Older participants were more likely to complete the program. The most potent predictor for non-recidivism was program completion, with non-completers 64% more likely to re-offend. Significant associations occurred between recidivism and the tests measuring skill improvement over time, chance locus of control pre- and post-program, and attitudes and values (Citizen Scale), partly supporting the theory behind the program